Primary care Adherence To Heart Failure guidelines IN Diagnosis, Evaluation and Routine management (PATHFINDER): A randomised controlled trial protocol - Dai, L.; Dorje, T.; Gootjes, J.; Shah, A.; Dembo, L.; Rankin, J.; Hillis, G.; Robinson, Suzanne; Atherton, J.J.; Jacques, Angela; Reid, Christopher; Maiorana, Andrew (2023)
Introduction General practitioners (GPs) routinely provide care for patients with heart failure (HF); however, adherence to management guidelines, including titrating medication to optimal dose, can be challenging in this setting. This study will evaluate the effectiveness of a multifaceted intervention to support adherence to HF management guidelines in primary care. Methods and analysis We will undertake a multicentre, parallel-group, randomised controlled trial of 200 participants with HF with reduced ejection fraction. Participants will be recruited during a hospital admission due to HF. Following hospital discharge, the intervention group will have follow-up with their GP scheduled at 1 week, 4 weeks and 3 months with the provision of a medication titration plan approved by a specialist HF cardiologist. The control group will receive usual care. The primary endpoint, assessed at 6 months, will be the difference between groups in the proportion of participants being prescribed five guideline-recommended treatments; (1) ACE inhibitor/angiotensin receptor blocker/angiotensin receptor neprilysin inhibitor at least 50% of target dose, (2) beta-blocker at least 50% of target dose, (3) mineralocorticoid receptor antagonist at any dose, (4) anticoagulation for patients diagnosed with atrial fibrillation, (5) referral to cardiac rehabilitation. Secondary outcomes will include functional capacity (6-minute walk test); quality of life (Kansas City Cardiomyopathy Questionnaire); depressive symptoms (Patient Health Questionnaire-2); self-care behaviour (Self-Care of Heart Failure Index). Resource utilisation will also be assessed. Ethics and dissemination Ethical approval was granted by the South Metropolitan Health Service Ethics Committee (RGS3531), with reciprocal approval at Curtin University (HRE2020-0322). Results will be disseminated via peer-reviewed publications and conferences. Trial registration number ACTRN12620001069943.